76 European facts and the global status report on road safety 2015. (1st September 2016) - Jackisch, Josephine; Sethi, Dinesh; Mitis, Francesco; Szymañski, Tomasz; Arra, Ian
Abstract : Background: Road traffic injuries are the leading cause of premature death in young people aged 5–29 years in the WHO European Region. The Decade of Action for Road Safety 2011–2020 was adopted by the United Nations General Assembly in 2010 to reduce the global toll of road traffic injuries by 2020. Methods: This fact sheet describes the status of road safety in 52 out of the 53 Member States of the WHO European Region, representing 95% of the Region's population. Experts from several sectors in each country reached consensus to complete a self-administered questionnaire. Furthermore, an independent expert analysis of national legislative documents was conducted. Results: In 2013, there were almost 85 000 deaths from road traffic injuries in the WHO European Region. Although the regional mortality rate is the lowest when compared to other WHO regions, with 9.3 deaths per 100 000 population, there are wide disparities in the rates of road traffic deaths between countries of the Region. This requires more systematic efforts if the global target of a 50% reduction in road crash deaths is to be achieved by 2020. Laws and practices on key risk factors such as regulating speed appropriate to road type, drink–driving, and use of seat belts, motorcycle helmets and child restraints are assessed to reduce the risk of road traffic injury. While 95% of the population in the Region is covered by comprehensive laws in line with best practice for seat belts, only 47% of the population is adequately protected by laws for speed, 45% for helmet use, 33% for drink–driving and 71% for use of child restraints. Conclusions: Many countries need to further strengthen their road safety legislation and enforcement in order to protect their populations, improve road user behaviour and reduce the number of crashes. Much can be gained from improving the safety of vehicles, having better road infrastructure and promoting sustainable physically active forms of mobility as alternatives to car use. Concerted policy efforts with systems approaches are needed to protect all road users in the Region.